An exploratory investigation into strategic groups and strategic blocks as an explanation for patterns of rivalry in the international airline industry - Galvin, Peter; Davies, Jennifer; Simons, Roland (Curtin University of Technology, 2002)
Strategic groups and strategic blocks offer alternative approaches to understanding patterns of intraindustry rivalry. Strategic groups have traditionally been conceptualised in terms of scope and resource commitments, whereas strategic block theory clusters firms together on the basis of the density of interorganisational linkages. This paper empirically tests the relative utility of the concepts of strategic groups and strategic blocks in the interpretation of patterns of rivalry across a number of international airline routes, ex-Australia. The findings suggest that both conceptual tools offer insight into the patterns of rivalry evidenced in the industry, however the number of strategic groups present on each route served as the better predictor of the degree of rivalry.Page